Integrasi Digital Pada E-LKPD Berbasis RME Untuk Mengoptimalkan Pemecahan Masalah Aljabar - Yudhi, Prima (Inovasi Pendidikan, 2025)
The abstraction of algebraic concepts presents a significant barrier to students' mathematical problem-solving proficiency. While Realistic Mathematics Education (RME) offers a pedagogical bridge by grounding mathematics in reality, its integration with digital media remains underexplored. This study aims to develop and critically analyze the mechanism of action of an Electronic Student Worksheet (E-LKPD) based on RME to optimize algebraic problem-solving skills. Utilizing the Research and Development (RD) methodology with the ADDIE framework, the study involved expert validation, practicality testing, and effectiveness assessment. Data analysis reveals a pedagogical alignment: the product achieved high validity scores (Material 87.5%, Media 80%, Language 86.67%) and practicality (88.17%). Crucially, the mechanism of action identified demonstrates that the E-LKPD's digital affordances successfully scaffold the mathematization process, transforming abstract symbols into tangible problem-solving tools. Consequently, student mastery increased significantly from an initial average of 26.92% to a post-intervention average of 91.15%, with 84.37% of students achieving classical mastery. This study confirms that the synergy between RME context and digital interactivity is a potent catalyst for mathematical understanding.